Pengaruh Lingkungan Belajar dan Media Sosial Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMKN 4 Kota Bengkulu - Esi Ayu Anggita; Suhirman Suhirman; Alimni Alimni (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The aim of this research is to determine the influence and how much influence the learning environment and use of Instagram social media have on learning achievement in PAI subjects and character. This type of research is field research, while the research approach is quantitative research with the method used is the survey method.  The research was carried out at SMK Negeri 4 Bengkulu City. The population in this study was 198 class XI students. With a sample of 66 students. Based on the results of the research, it can be concluded, first, that there is an influence of the Learning Environment on Learning Achievement, this is proven by the P value (significant) 0.000 < 0.05 which is smaller than 0.05 or thit < ttable 3.740 > 1.99834, meaning that Ho is rejected and Ha is accepted. . Second, there is an influence of social media use on learning achievement as evidenced by significant values thit < ttable (2.162 > 1.99834) and (sig > α = 0.009 < 0.050), so Ho is rejected and Ha is accepted. The correlation value (r) between the learning environment variables and social media is 0.466. Because this value is between 0.4-0.6, the relationship is said to be in the medium category, while the coefficient of determination is 0.544, meaning the contribution is 54.4%